Ambientaciones NDVI y predicibilidad de brechas de rendimientos de maíz en el NOA - Rodríguez, S.J.; Bustos, L.; Sopena, Roberto Alfredo; Diaz-Zorita, Martín; Martos, Gustavo Gabriel (INTA y Facultad de Ciencias Agropecuarias, Universidad Nacional de Córdoba, 2025)
Poster